Classroom teacher candidates' efficiency on the music culture and their music preferences - ARSLAN, AYŞEN (ELSEVIER SCIENCE BV, 2010)
With reference to Turkish Linguistic Society, Culture is defined as the total means of which the material and spiritual values are created in the historical and social development process that is used for conveying and creating these values to next generations and demonstrates the measurement of the domination of the people' natural and social environments. Anatolia has survived variety of prosperous cultures with its background of thousands of years. We have been developing being affected by the cultural prosperity as a nation living in this country. Our prosperity on the general culture has naturally affected our music culture. Classroom teacher candidates are responsible from educating future of persons who are eligible, contemporary, inquisitive and open to improve and question themselves. Thus, the teachers have to obtain same qualifications. This paper has studied that the candidate classroom teachers' efficiency on the music culture, their tastes in music and music preferences depended on their musical information and background acquired by their primary, secondary and high schools. The students from Marmara University studied in Ataturk Faculty of Education participated in this research at the beginning of their third term when they have not just taken the lessons relating to music and teaching of it. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Music; music culture; music education; kinds of music; classroom teacher candidate; developing taste in music